Recellularization of Bioengineered Scaffolds for Vascular Composite Allotransplantation - Adil, Aisha; Xu, Michael; Haykal, Siba (Frontiers in Surgery, 2022)
Traumatic injuries or cancer resection resulting in large volumetric soft tissue loss requires surgical reconstruction. Vascular composite allotransplantation (VCA) is an emerging reconstructive option that transfers multiple, complex tissues as a whole subunit from donor to recipient. Although promising, VCA is limited due to side effects of immunosuppression. Tissue-engineered scaffolds obtained by decellularization and recellularization hold great promise. Decellularization is a process that removes cellular materials while preserving the extracellular matrix architecture. Subsequent recellularization of these acellular scaffolds with recipient-specific cells can help circumvent adverse immune-mediated host responses and allow transplantation of allografts by reducing and possibly eliminating the need for immunosuppression. Recellularization of acellular tissue scaffolds is a technique that was first investigated and reported in whole organs. More recently, work has been performed to apply this technique to VCA. Additional work is needed to address barriers associated with tissue recellularization such as: cell type selection, cell distribution, and functionalization of the vasculature and musculature. These factors ultimately contribute to achieving tissue integration and viability following allotransplantation. The present work will review the current state-of-the-art in soft tissue scaffolds with specific emphasis on recellularization techniques. We will discuss biological and engineering process considerations, technical and scientific challenges, and the potential clinical impact of this technology to advance the field of VCA and reconstructive surgery.